Functional Analysis of Lexical Bundles in Doctor Talks in the Medical T.V. Series Grey’s Anatomy - Panthong , Panupan; Poonpon , Kornwipa (LEARN Journal: Language Education and Acquisition Research Network, 2020)
Lexical bundles, or recurrent word strings, are one of the key elements in increasing fluency of linguistic production and in mastering second language learning. In most previous works, lexical bundles were analyzed in specific disciplines. Little research paid attention to spoken discourse, particularly in doctors’ conversations (hereby referred to as “Doctor Talks”). This study aimed to investigate four-word lexical bundles in Doctor Talks and their operationalized functions. A Doctor Talk corpus was compiled from a famous medical TV series, Grey’s Anatomy, consisting of approximately one million running words (269 episodes from 12 seasons over 11 years). Four-word lexical bundles were identified, using WordSmith Tool version 7.0, and their discourse functions were analyzed, using Biber et al.’s (2004) functional taxonomy as a framework. The results reveal that 99 bundle types are present in the Doctor Talk corpus. Stance bundles are common in this spoken conversation corpus while lexical bundles articulating with special conversation features show the least proportion. The results also show some particular functions used in Doctor Talks as discourse organizers.